Recycling of spent coffee grounds for useful extracts and green composites. Issue 5 (13th January 2021) - Leow, Yihao; Yew, Pek Yin Michelle; Chee, Pei Lin; Loh, Xian Jun; Kai, Dan
Abstract : Spent coffee grounds are mostly discarded as waste. Here we recycle them for chemical compounds and as composite material fillers. Our study evaluated the chemical composition of coffee oil extracts and mechanical properties of composites formed. Abstract : Large amounts of spent coffee grounds (SCGs) are often discarded and there is a need to find alternative disposal methods due to environmental concerns. This project aims to develop sustainable materials by re-purposing spent coffee grounds (SCGs). Oil extraction was performed using different organic solvents and yielded approximately 10% coffee oil. Coffee oil contains potentially useful chemical compounds such as fatty acids and caffeine. They also exhibited antioxidant properties. Extracted SCGs (ESCGs) were blended with epoxy resin to form composites. ESCG composites displayed a general decrease in mechanical properties relative to epoxy. However, improvements were observed when comparing ESCG composites and SCG composites. The greatest improvement belongs to epoxy composite filled with acetone-ESCGs, where the tensile strength, flexural modulus and flexural strength increased to 23.4 MPa, 3.02 GPa and 42.9 MPa respectively. This study presents a way to exploit waste materials which contributes to the goal of sustainability.